Prevalence of protein intake below recommended in community‐dwelling older adults: a meta‐analysis across cohorts from the PROMISS consortium - Hengeveld, Linda M. (2020)
European Horizon 2020 PROMISS Project ‘PRevention Of Malnutrition In Senior Subjects in the EU’, (grant agreement no. 678732). The content only reflects the author’s view and the commission is not responsible for any use that may be made of the information it contains.